Design Of Improved Voltage Mode Control Circuits For Fast Transient Response In Switch-Mode Power Supplies - Sjegadeson, Jegandren (2009)
The main objective of this project was to design a 300W, 25V half bridge dc-dc converter switch-mode power supply (SMPS). A fast transient response to a step load change is very essential in a power supply for most applications. The transient responseof the output voltage can be improved by means of dc-dc converter and feedback control methods.